Patterns of Land Market Developments in Transition - Jo Swinnen; Liesbet Vranken (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
Transition countries provide a natural experiment to study the development of land markets. This paper provides survey-evidence of the variation in the development of land markets, identifies a series of patterns, and provides a set of hypotheses to explain these variations in land market development.
Keywords: 330; Landwirtschaftliche Immobilien; Systemtransformation; Ländliche Entwicklung; Wirtschaftliche Anpassung; Immobilienmarkt; Transformationsstaaten; Osteuropa; Südosteuropa